2019
DOI: 10.31557/apjcp.2019.20.10.3129
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stage Longitudinal Change of Quality of Life from Pre- to 3 Months after Surgical Treatment in Head and Neck Cancer Patients

Abstract: Purpose: Head and neck cancer (HNC) patients experience various posttreatment side effects that decrease quality of life (QOL). Some previous study reported that QOL of HHC patients were returned baseline (before treatment) after a year post treatment. However, acute stage longitudinal changes of QOL in HNC patients remains unclear. This point might be important for early reintegration of HNC patients. This study aimed to investigate the acute stage longitudinal change of the relationship between QOL and oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…A previous study reported that LC in patients with HNC returned to the BL 3 months following treatment [ 32 ]. The primary tumor site in their study included the tongue, pharynx, or maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that LC in patients with HNC returned to the BL 3 months following treatment [ 32 ]. The primary tumor site in their study included the tongue, pharynx, or maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that LC in patients with HNC returned to the BL 3 months following treatment [30]. The primary tumor site in their study included the tongue, pharynx, or maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the FOIS has already been reported for its reproducibility and validity [ 24 ]. Several studies have used the FOIS for HNC patients [ 25 , 26 ], so it was also adopted in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical procedures varied among patients, and some patients developed mucositis due to chemotherapy and/or radiation therapy after surgical resection [ 25 , 26 ]. Data analyses with defects were performed using a linear mixing model, but there were some cases in which a postoperative evaluation was impossible due to dysphagia symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation